Good Governance Indonesian Forestry: A Fair Justice System - Dwiputri, Inayati Nuraini; Prastiwi, Lustina Fajar; Abbas, Muhammad Hasyim Ibnu; Sumanto, Agus; Isupova, Ekaterina (CV. Literasi Indonesia, 2025)
Many studies have identified the relationship between corruption and the socio-economic life of society. Generally, the results of research indicate that corruption is detrimental to the economy and society. Corruption can create burdens for society, companies, and the government. Therefore, the impact of corruption is calculated as a state loss. Corruption in the form of embezzlement occurs frequently in both the public and private sectors. Bribery and extortion are common in the public sector. Several studies related to corruption have identified the effects of corruption on social and economic life. Other studies have identified the implementation of corruption in the public and private sectors. This study will discuss the law enforcement of corruption. It identified decisions of law enforcement at the Supreme Court, specifically regarding corruption in the forestry sector. This study used content analysis to identify Supreme Court decision documents. The results indicate that a significant amount of corruption results from illegal land transfer and forest land ownership. The content analysis indicated that the Supreme Court's judicial system, particularly regarding corruption in the forestry sector, is quite fair. However, further analysis is needed regarding the sentences given to the defendants to decrease corruption.